The importance of public support in the implementation of green transportation in smart cities using smart vehicle bicycle communication transport. Issue 5 (23rd November 2020) - Li, Ning; R., Parthasarathy; Padwal, Harshila H.
Abstract : Purpose: Smart mobility is a major guideline in the development of Smart Cities' transport systems and management. The issue of transition into green, secure and sustainable transport modes, such as using bicycles, should be implemented in this case, along with the subjectivism of management. Design/methodology/approach: The proposed technology reflects the Smart Bicycle vehicle model, which tracks cyclists and weather conditions and turns to electric motors in critical circumstances. Findings: This reduces the physical load and battery consumption of cyclists which affects the Smart Cities' ecology positively. Originality/value: In Smart Vehicle Bicycle Communication Transport, the vehicle movement optimization technique is used for traffic scenarios to analyze traffic signaling systems that give better results in variable and dense traffic conditions.